Pet ownership is associated with harmful alcohol use among a cohort of people with HIV: a brief research report - Applebaum, Jennifer W.; McDonald, Shelby E.; Porges, Eric C.; Widmeyer, Maya; Fabelo, Humberto E.; Kertes, Darlene A.; Cook, Robert L. (Frontiers in Psychiatry, 2023)
Research suggests that people with HIV (PWH), who are at high risk for alcohol and substance use, may rely on relationships with pets for companionship and stress relief. There may be common mechanisms underlying both substance use and attachment to pets. The purpose of this brief research report was to compare alcohol and substance use behaviors between pet owners and non-owners among a cohort of PWH. Participants (n=735) in a survey study of PWH in Florida were asked about their alcohol and substance use behaviors, whether they owned a pet, and their sociodemographic characteristics. We used bivariate analyses and logistic regression to examine differences in alcohol and substance use behaviors between pet owners and non-owners. Pet owners had higher mean AUDIT scores than non-owners (Mpet=5, Mnopet=4, z=-3.07, p=0.002). Pet owners were more likely than non-owners to use alcohol in a harmful or hazardous way (AUDIT score ≥8), above and beyond sociodemographic characteristics (OR=1.65, p=0.052). Pet owners were more likely to have ever used most substances than non-owners, and more likely to currently use alcohol (X 2 (1)=12.97, p=0.000), marijuana or hashish (X 2 (1)=6.82, p=0.009), and amyl nitrate/poppers (X 2 (1)=11.18, p=0.001). Pet owners may be more likely to use alcohol and other substances at higher rates than non-owners. Reasons for owning a pet and using substances may be similar, such as coping with stress.